The R.B.Q. (Rational, Behavioral and Quantified) Model - Challoumis, Constantinos (Ekonomika, 2019)
[full article and abstract in English] This paper is about the classic methods used in the analysis of economics. More precisely, the R.B.Q. (Rational, Behavioral, and Quantified) model is about rational economics and behavioral economic analysis in conjunction with the quantification procedure (Q.E. method). Therefore, in this work are submitted the most common methodological approaches used in economics including a form of their combination. What follows is a critical examination that extendedly scrutinizes the terminology of axiomatic methods. One of the aims of this paper to represent the special characteristics of rational economics in comparison to the case of behavioral economics. Then provided is an analysis wherein the issues relevant to this are represented, and on the basis of which the main differences between the two concepts are showed. Hence, the aim here is to show the crucial attributes of these concepts. This study also uses a quantification method to show the behavior of these two economic theories within their relation to one another, demonstrating a complete view of them in a single economic model.